Somatotype, age, and neuromuscular performance in elite youth football players - Androulakis, N.; Tsiakiris, C.; Koundourakis, N. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: Somatotype has been linked to physical performance in youth athletes, but its independent contribution to power development, particularly in relation to biological maturity, remains underexplored. This study examined whether somatotype and age independently influence neuromuscular performance in elite youth football players and whether these effects persist after normalization for body mass.